Efficacy of the FIFA 11+ warm-up programme in male youth football: A cluster randomised controlled trial - Owoeye, O. B. A.; Akinbo, S. R. A.; Tella, B. A.; Olawale, O. A. (Journal of Sports Science & Medicine, 2014)
The FIFA 11+ is a structured warm-up programme specially designed to prevent injuries among football players from age 14 years and above. However, studies to prove its efficacy are generally few and it is yet to be tested in male youth footballers and among African players. The purpose of the study was to examine the efficacy of the FIFA 11+ programme in reducing the risk of injuries among male youth football players of the Lagos Junior League. A cluster randomised controlled trial was conducted. All the 20 teams (414 players aged 14 -19 years) in the Premier League division were block-randomised into either an intervention (INT) or a control (CON) group. The INT group performed the FIFA 11+ exercises as warm-up during training sessions and the CON group performed usual warm-up. Participating teams were prospectively followed through an entire league season of 6 months in which they were visited every week to assess injured players for time-loss injuries in both groups. The primary outcomes were any injury to the players, injuries by type of exposure and injuries specific to the lower extremities. The secondary outcomes were injuries reported by body location, aetiology, mechanism and severity. In total, 130 injuries were recorded affecting 104 (25%) of the 416 players. Team and player compliance with the INT was 60% and 74% respectively. Based on the primary outcome measures of the study, the FIFA 11+ programme significantly reduced the overall rate of injury in the INT group by 41% [RR = 0.59 (95% CI: 0.40 - 0.86; p = 0.006)] and all lower extremity injuries by 48% [RR = 0.52 (95% CI: 0.34 - 0.82; p = 0.004)]. However, the rate of injury reduction based on secondary outcomes mostly did not reach the level of statistical significance. The FIFA 11+ programme is effective in reducing the rates of injuries in male youth football players.